70 Trichobezoar: the importance of a multidisciplinary approach. (11th October 2021) - Francisco, Catarina Macedo; Pereira, Pedro; Silva, Íris Santos; Guerra, Pedro; Gonzalez, Isabel; Pissarra, António P
Abstract : Introduction: Abdominal pain is one of the most frequent causes of pediatric Hospital admission, and therefore is frequently overlooked; its cause is usually attributed to cramps or constipation. Nevertheless, a thorough investigation should always be performed. Case Study: 14 year-old girl, institutionalized, admitted to the Emergency Department due to abdominal pain, in the context of constipation, which was already known. The patient has a history of Psychiatric disease, and is taking Risperidone 0.5mg once daily. The patient did an abdominal radiography that showed abdominal distension and presence of a large amount of feces. After bowel enema, the pain persisted, and due to the recurrent symptoms, she was hospitalized. Her blood tests demonstrated only Anemia (Hb: 10g/dL; MCV: 74.7 fL; MCH: 20.9 pg; CHCM: 27.9 g/dL), low total proteins: 5.18 g/dL; and low Albumin: 3.17 g/dL. Her abdominal pain was progressively increasing, and she then performed an abdominal CT scan, which showed a large mass in the stomach extending up to the pylorus, with extra-abdominal gas adjacent to the gastric antrum. The hypothesis of trichobezoar with gastric perforation was primarily considered. A small pleural effusion on the left side was also described. Surgical approach was performed and a large trichobezoar, of about 20cm, was successfully removed. Anterior stomach perforation and chemical peritonitis was also found. After surgery, the patient then admitted to suffer from Tricophagy, as a part o f her Psychiatric condition. During recovery, the pleural effusion increased in size, despite intravenous albumin therapy and drainage was performed. She was then discharged to her institution after a week. Currently, her bowel movement is completely restored, and she is taking iron oral supplements. She maintains follow-up at our outpatient clinic, maintaining slight chest pain of pleuritic character. Conclusion: Among adolescents, the frequency of psychosomatic symptoms is common. Nevertheless, and as we can see in this case, sometimes the etiology of abdominal pain can be quite serious, and even fatal if left untreated. We should always value the overall clinical state of the patient in order to guide our medical approach. The collaboration between Pediatrics, Radiology and General Surgery was vital for a successful diagnosis and treatment.